Hubungan Sikap Lansia Hipertensi Dengan Pelaksanaan Self Management Di Puskesmas Tigo Baleh Kota Bukittinggi - Sovia Khoirun Nisa; Izzati, Wisnatul; Andriani, Aida (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2025)
Hypertension is a degenerative disease with a high mortality rate that reduces quality of life and productivity, especially among the elderly, where attitude plays an important role in self-management. This study aimed to examine the relationship between elderly attitudes and self-management at the Tigo Baleh Bukittinggi Community Health Center using a quantitative cross-sectional design with purposive sampling of 169 respondents. Data were collected through an attitude questionnaire and the Hypertension Self-Management Behavior Questionnaire (HSMBQ). Results showed that 100 respondents (59.4%) had a fair attitude, while 84 respondents (49.7%) demonstrated good self-management. Statistical analysis revealed a p-value of 0.00 (p < 0.05) and correlation coefficient r = 0.502, indicating a significant moderate relationship between attitude and self-management. The conclusion is that better self-management among hypertensive elderly is associated with more positive attitudes. It is expected that the Tigo Baleh Health Center can use these findings to improve the daily attitudes and practices of elderly patients with hypertension.